2009
DOI: 10.1080/09593980902776613
|View full text |Cite
|
Sign up to set email alerts
|

A grounded-theory investigation of patient education in physical therapy practice

Abstract: Patient education is a critical component of physical therapy and is used frequently in practice. Research describing the practice of patient education in physical therapy is scarce, however. Qualitative research methods can be used to describe the practice of patient education in physical therapy and to identify supportive theory. This study describes the practice of patient education grounded in data obtained from nine physical therapists in three settings: outpatient, acute care, and inpatient rehabilitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 18 publications
2
22
0
7
Order By: Relevance
“…Previous research describing patient education within physiotherapy has identified central themes of promoting patient self-care and empowerment of the patient towards self-management (Rindflesch, 2009). Our results support these concepts where nearly all respondents in our study reported frequently teaching selfmanagement strategies and reported this activity to be important.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Previous research describing patient education within physiotherapy has identified central themes of promoting patient self-care and empowerment of the patient towards self-management (Rindflesch, 2009). Our results support these concepts where nearly all respondents in our study reported frequently teaching selfmanagement strategies and reported this activity to be important.…”
Section: Discussionsupporting
confidence: 86%
“…Early survey based research reports that 99% of physiotherapists perceive patient education as an important skill within their practice and 98% report participating in individual patient education as part of their patient care (May, 1983). More recent studies exploring patient education report that physiotherapists frequently engage in patient education centred on the principles of adult learning (Bresse and French, 2012) and self-efficacy (Rindflesch, 2009). Despite this, reports suggests physiotherapists do not routinely engage in education relating to health promotion and stress reduction (Sluijs et al, 1991;Fruth et al, 1998;Rindflesch, 2009), and find it challenging to provide explanations of cause of symptoms for common patient populations (Slade et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations